PENGARUH INTENSITAS MODAL DAN LEVERAGE TERHADAP KINERJA KEUANGAN DENGAN NILAI PERUSAHAAN SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019-2021 - Safitri, Vira Dianita; Karnadi, Karnadi; Subaida, Ida (Jurnal Mahasiswa Entrepreneurship (JME), 2023)
This study aims to determine the effect of capital intensity and leverage on company value through financial performance as an intervening variable in food and beverage companies listed on the Indonesia Stock Exchange for the 2019-2021 periods. This study used a sample of 11 food and beverage companies with a three-year period from 2019-2021 which were selected using a purposive sampling technique. Collection techniques are obtained through the official IDX website: www.idx.co.id. Data analysis and hypothesis testing in this study used the Smart PLS 3.0 Equation Method (Partial Least Square). The results of the direct effect hypothesis test using the Smart PLS 3.0 application indicate that capital intensity has a significant effect on financial performance. Leverage has a significant effect on financial performance. Capital intensity has a significant effect on company value. Leverage has a significant effect on company value. Financial performance has a significant effect on company value. Capital intensity has a significant effect on company value through financial performance. Leverage has a significant effect on company value through financial performance.